Re-Visitation of “The Epic of Sunjata”: Using Virtual Reality (VR) as a Method of Instruction - Ladji Sacko (European Scientific Journal, ESJ, 2023)
This paper focuses on students learning literature in the classroom, presenting it as a challenging “out of culture experience”. The expanded world history curriculum now encompasses a global perspective, moving beyond a European focus. To engage with topics beyond Europe, students must cultivate approaches that extend beyond mere memorization of dates and locations. One approach to adopt is the use of VR to expose students to literature from outside Africa and Europe (VR). A narrative such as "The Epic of Sunjata" may teach valuable lessons, as it will pique students' curiosity about subjects outside Africa and Europe.